Μορφοποίηση δεσμών φωτός σε διαφανή υλικά χρησιμοποιώντας λέιζερ Φεμτοδευτερολέπτου - Ιωάννου, Ανδρέας (Τμήμα Ηλεκτρολόγων Μηχανικών και Μηχανικών Ηλεκτρονικών Υπολογιστών και Πληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
This project was undertaken in order to investigate the potential for generating femtosecond-laser inscribed optical elements that modify the properties of Gaussian optical beams. The optical elements modify the phase of the traversing optical beams, and are inscribed in both planar samples and at the output end of optical fibers. Our goal is to examine whether it is possible to produce various specialized light beams in a simple and efficient manner using readily available transparent materials. Our ultimate objective is the production and verification of elements that produce non-diffracting light beams, such as Airy and Bessel beams, whilst also producing elements that generate diffraction and optical vortices. The final goal of transferring the technology to single mode optical fibers and particularly challenging, as the core diameter is less than 10μm. The inscription that is undertaken using the FSL was implemented with the use of algorithms that were generated using the programming language G-Code in combination with the specialized software (Motion Composer). The intensity of the laser and the inscription speed play key roles in the characteristics of the inscribed structures, affecting in particular the inscription depth. Thus having precise control of the inscribed masks is essential in yielding the desired results. With the completion of this thesis we conclude that we have achieved our goals, since a large part of our efforts have brought more than satisfactory results. As for our ultimate goal, the construction of non-diffracted light beams Airy in optical fibres, we have results that are very promising and under further investigation. Their production on fused silica is clearer, allowing us to study their properties and better understand their nature.
Keywords: Femtosecond laser; Light beams; Airy beams; Bessel beams; G-Code; Motion Composer; Λέιζερ φεμτοδευτερολέπτου (FSL); Δέσμη Φωτός; Διαφανή υλικά